Unveiling the anti-aging of radix saposhnikoviae: A metabolomic study in Drosophila - Liwei Jia; Xianglin An; Yan Liu; Xin Meng (PLoS ONE, 2025)
Aging is characterized by a progressive decline in physiological functions and an increased susceptibility to age-related diseases, yet effective interventions remain limited. Recent advancements in understanding the molecular mechanisms of aging have highlighted pathways such as insulin-like signaling, mTOR, and sirtuins. Meanwhile, traditional medicinal herbs are increasingly recognized for their potential to modulate these pathways. However, comprehensive analyses investigating how these herbs influence multiple aging-related metabolic pathways simultaneously remain scarce. This study examines the anti-aging and antioxidant effects of Radix Saposhnikoviae (Fangfeng) through metabolomic analysis using Drosophila melanogaster as a model organism. Our findings indicate that different Fangfeng preparations significantly extended the lifespan of Drosophila to varying extents. Utilizing nuclear magnetic resonance (NMR) metabolomics, we identified key metabolic pathways modulated by Fangfeng, including those related to energy metabolism, oxidative stress response, lipid metabolism, protein homeostasis, and inflammatory processes-each closely associated with aging. The results revealed significant regulation of these pathways, particularly those involved in oxidative stress and energy homeostasis, which are central to the aging process. These findings underscore the potential of Radix Saposhnikoviae as a promising medicinal herb for modulating key biochemical pathways associated with aging and oxidative stress. This study provides a scientific basis for the integration of traditional herbal medicine into contemporary anti-aging strategies, contributing to the expanding field of aging research.